Human development and faith life-cycle stages of body, mind, and soul - Kelcourse, Felicity (St. Louis : Chalice Press, 2015)
This book, now in its second edition, brings together the best available understandings of human development from a multidisciplinary perspective. Uniquely inclusive of the moral and faith dimensions of context and life-cycle development, Human Development and Faith examines the interplay of mind, body, family, community, and soul at every stage of development. It addresses two central questions: What are the "good-enough" conditions of parenting, family, and community in each phase of life, from birth to death, that support growth and development? What gives life adequate meaning as developm.
9. Early Adolescence: Venturing toward a Different World10. Identity in Middle and Late Adolescence; 11. The Differentiation of Self and Faith in Young Adulthood: Launching, Coupling, and Becoming Parents; 12. The Middle Years; 13. Faith and Development in Late Adulthood; 14. The Wages of Dying: Catastrophe Transformed; References and Bibliography; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; R; S; T; U; V; W; Y; Z.
Print version record.
Keywords: Faith development; Faith; Faith development; Faith; Life cycle, Human -- Religious aspects -- Christianity; Religion; RELIGION -- Christian Life -- General; Electronic books